2022
DOI: 10.1542/peds.2021-055956
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome Following SARS-CoV-2 Vaccination in Two Children

Abstract: This report presents 2 pediatric cases of multisystem inflammatory syndrome in children/adults (MIS-C/A) post-SARS-CoV-2 Vaccination (MIS-V). Both children presented with MIS-V within 6 weeks of receiving their first and only dose of Pfizer/BioNTech’s SARS-CoV-2 vaccine. The first patient had symptoms of MIS-C/A with peri-myocarditis and shock, and the second one had classic Kawasaki Disease (KD) features. Both responded well to intravenous immunoglobulins and/or systemic corticosteroids. Both children were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Recently, a multisystem inflammatory syndrome following SARS-CoV-2 vaccination (MIS-V) both in adults [ 7 ] and children [ 8 , 9 ] has been described, raising some concerns in the scientific community which, in conjunction with international regulatory agencies, is actively monitoring this condition [ 8 , 9 ]. MIS-V is a rare entity, and the exact incidence, prevalence and pathophysiology are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a multisystem inflammatory syndrome following SARS-CoV-2 vaccination (MIS-V) both in adults [ 7 ] and children [ 8 , 9 ] has been described, raising some concerns in the scientific community which, in conjunction with international regulatory agencies, is actively monitoring this condition [ 8 , 9 ]. MIS-V is a rare entity, and the exact incidence, prevalence and pathophysiology are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, neurological adverse events following vaccination are generally mild and transient, although rare major neurological complications, such as cerebral venous sinus thrombosis, Bell's palsy, acute transverse myelitis, acute disseminated encephalomyelitis, and acute demyelinating polyneuropathy, have been described [5,6] Recently, a multisystem inflammatory syndrome following SARS-CoV-2 vaccination (MIS-V) both in adults [7] and children [8,9] has been described, raising some concerns in the scientific community which, in conjunction with international regulatory agencies, is actively monitoring this condition [8,9]. MIS-V is a rare entity, and the exact incidence, prevalence and pathophysiology are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Multisystem MIS following COVID-19 vaccination (MIS-V) remain rare event [186], but it is a serious adverse event. There have been identified 12 cases of hyper-inflammatory syndrome following COVID-19 mRNA vaccines (now MIS-V) in 12-17-year-old children in France, with multisystemic involvement [187], and two pediatric cases with neurological involvement in Italy [186]. Two other cases have recently been described…”
Section: Multisystem Inflammatory Syndromes (Mis)mentioning
confidence: 99%
“…Multisystem Inflammatory Syndrome in children (MIS-C) and adult (MIS-A) are late complication of SARS-CoV-2 infection [181][182][183][184][185]. MIS following COVID-19 mRNA vaccines (MIS-V) it is a serious adverse event and there are many pediatric case reports that begin 4-6 weeks after the first vaccine dose [186][187][188].…”
mentioning
confidence: 99%
“…Considering that vaccination can increase only antispike antibodies, it has been confirmed that the boy developed MIS-C following the infection [109]. In addition, children who developed MIS-C because of vaccination were also reported, which has been confirmed by sub-antibody measurements [110,111]. Given the rarity of the disease and these paradoxical events, the harm-benefit balance of the vaccines against MIS-C remains somewhat unclear.…”
Section: Preventionmentioning
confidence: 99%